Suppression of abnormal grain growth in friction-stir welded Al–Cu–Mg alloy by lowering of welding temperature. (15th April 2021) - Zuiko, Ivan S.; Mironov, Sergey; Betsofen, Sergey; Kaibyshev, Rustam
Abstract: The effect of welding temperature on thermal stability of friction-stir welded (FSWed) 2519 aluminum alloy was investigated. A lowering of the welding temperature below the particle dissolution threshold was shown to be a very effective way for suppression of abnormal grain growth during post-weld solution treatment. This effect was attributed to a prevention of the welded material from precipitation of fine dispersoids during subsequent annealing which resulted in relatively low Zener pressure and thus provided an activation of the apparently-normal grain-growth mechanism. This phenomenon was demonstrated for the first time and could be used as a processing strategy to improve thermal stability of FSWed heat-treatable alloys.